Influence of rule changes on shooting performance in balanced matches between two European water polo championship - Argudo, F. M.; García Marín, P.; Borges Hernández, P. J.; Ruíz-Lara, E. (International Journal of Performance Analysis in Sport, 2021)
The aim of this study was to compare the influence of rules changes on shots performance in balanced matches considering two male European Championship with different rules. All shots made in matches with a final score with differences of three goals or less in 27th European Championship in 2006 (Belgrade, Serbia) and 34th European Championship in 2020 (Budapest, Hungary) were analysed in the present study. The total sample was composed of 2,493 shots (1,115 in Belgrade Championship and 1,378 in Budapest). The study was developed with an observational design. The reliability between the observers was verified using the kappa agreement index, ensuring that in all cases this value was greater than .85. There are differences in the number of shots taken between the two championships. There is a lower number of shots after a foul, as well as drive shot with rebound on short post and large post in inequality situation. There are fewer shots in the counterattack and more shots in inequality. In both micro situations, there are more shots from the left side and less shot with feint or center shots.